Perspectives On Digital Inclusion: The Participation Of Seniors In Social Networks - Pinheiro, Ana (2020)
The research presented in this article had as main aims: a) to know the use of social networks by a group of elderly people, as well as b) to understand the representations of this target audience on the use of this type of technology during their daily lives. The qualitative study had a first phase of exploratory collection, which consisted of randomly analysing public profiles of Facebook users over 65 years of age. Taking this into account, categories of analysis were defined which catered for a more in-depth look at 6 profiles, of 6 elderly people, which have been observed over 6 months. At the same time, 8 interviews were undertaken with individuals of the same age group, users of social networks, in order to understand their representations on the topic. The data collected allowed us to understand some aspects of the use of social networks by this public, namely the lack of care in the disclosure of personal information, the integration of the use of Facebook in the daily lives of the elderly, the use of the network as a means of approach relatives, either to learn how it works or to contact those who are far away.